STUDI EKSEGESIS “TAKUT AKAN TUHAN SEBAGAI PERMULAAN PENGETAHUAN”: KAJIAN TERHADAP AMSAL 1:7 DALAM PERSPEKTIF HIKMAT PERJANJIAN LAMA - Alex Rangan; Melisa eldayani; Kori. R (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
This study aims to examine the theological and epistemological meaning of the phrase “the fear of the LORD is the beginning of knowledge” in Proverbs 1:7 through an exegetical approach within the perspective of Old Testament wisdom. The main problem of this study is how the concept of “fear of the LORD” is understood in the context of the Hebrew text and how the concept functions as a foundation for knowledge and wisdom in the biblical tradition. The method used is a qualitative approach with a literature review that focuses on the analysis of the Hebrew biblical text, the study of Old Testament theological literature, and historical-critical and thematic analysis of the main concepts in the text. The results of the study show that “fear of the LORD” does not refer to emotional fear, but rather an attitude of respect, obedience, and recognition of God’s sovereignty as the source of wisdom. This concept serves as an epistemological foundation that places the human relationship with God as the starting point of true knowledge. Moreover, the human response to wisdom determines whether a person grows in wisdom or remains in ignorance.